Filling the Atlantic coastal tree-ring reconstruction gap: A 195-year record of growing season discharge of the Sainte-Anne River, Gaspésie, Québec, Canada - A.V. Pace; J.-M. St-Jacques; D.D. Noel; G. Fortin (Journal of Hydrology: Regional Studies)
Study region: We present a coastal river reconstruction between the Hudson River and north-central Québec, filling a substantial hiatus between 41° N and 53° N along the Atlantic North American margin, and adding to the four existing Atlantic coastal river basins with reconstructions. Study focus: This study produced a 195-year tree-ring based reconstruction of growing season flow of the Sainte-Anne River, Gaspésie, Québec, Canada. Our nested reconstruction (maximum R2 = 0.53, maximum RE = 0.32) was based upon eight site chronologies where snowpack limits the length of the growing season. New hydrological insights for the region: We found declining extreme May-July flows since 1937, suggesting a reduction of snowpack in this alpine region in the northern Appalachians. Our Gaspésie reconstruction showed droughts and pluvials in common with multi-centennial river/moisture reconstructions along the Atlantic Seaboard from New York, Delaware and Maryland and from north-central Québec. A principal components analysis (PCA) and correlation analysis with GRUN (the 5°x5° gridded multi-model ensemble of runoff of Ghiggi et al. (2019. Earth Syst. Sci. Data. 11, (1655–1674) showed common modes of variability through-out this broader region. While energy-limited tree-ring chronologies are well-known in western North America, they are poorly known in eastern North America. We found energy-limited snow proxy sites in this region noted for its high snowfall. This reconstruction may prove useful for wildlife, fisheries and hydroelectric reservoir management.